Corporate Taxation and Financial Strategies Under Asymmetric Information - Francesco Cohen; Alessandro Fedele; Paolo Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this article we study the corporate tax effects on credit market equilibria. In particular, we develop a model that accounts for five pieces of evidence: i) the existence of a tax incentive to borrow, ii) the negative relationship between leverage and profitability, iii) the existence of asymmetric information in credit markets, iv) the screening activity of lenders and v) the business cycle effects on the spread between the high-yield and the investment-grade interest rates on corporate loans. Assuming the existence of two types of firms, we show that either a separating or a pooling credit market equilibrium can arise. More importantly, the equilibrium is crucially affected by corporate taxation. Given these results, we also provide a welfare analysis and discuss corporate tax policy implications.
Keywords: H20; D82; 330; capital structure; corporate taxation; asymmetric information